Effect of liming on the availability of three rock phosphate sources in two West African Ultisols - Juo, A.S.R.; Kang, B.T. (1979)
The relative effectiveness of two African rock phosphate (Morocco rock, MR and Togo rock, TR) was compared with the more reactive North Carolina rock phosphate (NCR) and with Triple superphosphate (TSP) in greenhouse using two strongly acidic Ultisols from southern Nigeria with and without application of lime. Without liming, the relative effectiveness of the four P sources is in the order of NCR>TSP>MR>TR; while with liming, the sequence becomes: TSP≥NCR>MR>TR. Liming soils to pH near 5.5 depressed P uptake by plant from the rock P sources but increased P uptake from TSP. Morocco and Togo rocks are poor sources of P for direct application under both limed and unlimed conditions.